Physalin B attenuates liver fibrosis via suppressing LAP2α–HDAC1‐mediated deacetylation of the transcription factor GLI1 and hepatic stellate cell activation. (21st May 2021) - Zhu, Xiaoyun; Ye, Shengtao; Yu, Dongke; Zhang, Yanqiu; Li, Jie; Zhang, Meihui; Leng, Yingrong; Yang, Ting; Luo, Jianguang; Chen, Xinlin; Zhang, Hao; Kong, Lingyi
Abstract : Background and Purpose: Liver fibrosis is one of the leading causes of morbidity and mortality worldwide but lacks any acceptable therapy. The transcription factor glioma‐associated oncogene homologue 1 (GLI1) is a potentially important therapeutic target in liver fibrosis. This study investigates the anti‐fibrotic activities and potential mechanisms of the phytochemical, physalin B. Experimental Approach: Two mouse models (CCl4 challenge and bile duct ligation) were used to assess antifibrotic effects of physalin B in vivo. Mouse primary hepatic stellate cells (pHSCs) and human HSC line LX‐2 also served as in vitro liver fibrosis models. Liver fibrogenic genes, GLI1 and GLI1 downstream genes were examined using Western blot and quantitative real‐time PCR (qRT‐PCR). GLI1 acetylation and LAP2α–HDAC1 interaction were analysed by co‐immunoprecipitation. Key Results: In vivo, physalin B administration attenuated hepatic histopathological injury and collagen accumulation and decreased expression of fibrogenic genes. Physalin B dose‐dependently suppressed fibrotic marker expression in LX‐2 cells and mouse pHSCs. Mechanistic studies showed that physalin B inhibited GLI activity by non‐canonical Hedgehog signalling. Physalin B blocked formation of lamina‐associated polypeptide 2α (LAP2α)/histone deacetylase 1 (HDAC1) complexes, thus inhibiting HDAC1‐mediated GLI1 deacetylation. Physalin B up‐regulated acetylation of GLI1, down‐regulated expression of GLI1 and subsequently inhibited HSC activation. Conclusion and Implications: Physalin B exerted potent antifibrotic effects in vitro and in vivo by disrupting LAP2α/HDAC1 complexes, increasing GLI1 acetylation and inactivating GLI1. This indicates that the phytochemical physalin B may be a potential therapeutic candidate for the treatment of liver fibrosis.